Three-Dimensional Skull Model for Endoscopic Skull Base Surgical Training. (16th November 2020) - Nebor, Ivanna; Hussein, Ahmed; Montemagno, Kora; Fumagalli, Rebecca; Labiad, Ikrame; Anderson, Zoe; Xu, Alice; Sedaghat, Ahmad; Patil, Yash; Forbes, Jonathan A
Abstract: INTRODUCTION: The expanded endonasal approach has provided access and a relatively new visualization of the ventral skull base. Unfortunately, post-operative cerebrospinal fluid leakage has limited the use of this approach. Currently, existing methods for closing defects after such approach do not provide reliable results and dura suturing is one of the methodic shows high rate CSF prevention. However, the technique is time-consuming, making it an unfavorable closing procedure among surgeons. METHODS: The training model was created using Ultimaker 2+ 3D printer. CT scan from real patient in DICOM format was used for skull modeling. Dura mater was mimicked by fresh chicken skin fixed by screws. Residents and attending were asked to perform suturing using 2D 0° endoscope without fixation and barbed sutures methodic. Participants were asked a series of questions after using the model regarding its usefulness in their endoscopic training and its potential to improve anatomic knowledge. RESULTS: 26 participants took part in the research. They were divided in two main groups: Group A included 22 residents and fellows in training and Group B consisted of 2 otolaryngologists and 2 neurosurgeons with 10–20 years of experience. 68% of Group A believed that the model is useful in their endoscopic training while 45% said that the 3D skull model would enhance their dural suturing abilities. 3 experts in group B thought that the model was very similar to the real human anatomy which would enhance anyone's endoscopic surgical ability regardless of their training experience. CONCLUSION: Our team thought by replicating a cheap and more readily available Skull model -specially for those in training- without the need to have costly cadaveric dissection laboratories would surely enhance the surgeons microsurgical skills and anatomic knowledge. Dural suturing model could potentially be used to enhance the residents and younger surgeons' endoscopic skills and endonasal suturing. Further replication and modification of the current model would serve better understanding of endoscopic surgery basics and enhance surgical.